Tindakan Kekerasan terhadap Perempuan dalam Perspektif Sosio-Yuridis - Harkristuti Harkrisnowo (Fakultas Hukum Universitas Islam Indonesia, 2000)
As aform of crime, Durkheim's opinion, the woman violence as well as other forms of crime seems continuously to appear In this world. However, it does not mean that the frecuency, prevalence, and incidence of the women violence cannot be declined. To overcome this problem, both the juridical attempt and awareness of societies are necessary to conduct Without public participation, the violence is Impossible to be to change the societies